Ascending Cholangitis secondary to migrated embolization coil of gastroduodenal artery pseudo-aneurysm a case report - Zaafouri, Haithem (BMC Surg, 2017)
BACKGROUND: Gastroduodenalartery (GDA) pseudo-aneurysms are very rare. Their clinical importance lies in the eventuality of rupture, causing bleeding and ultimately exsanguination. CASE PRESENTATION: We report the case of a man, with prior history of biliary surgery, presenting with haemobilia secondary to a rupture of GDA pseudo-aneurysm eroding the main bile duct. The patient was treated with coil embolization. This technique is considered to be safe. However, on the long term, some complications may occur. In our case, the patient presented with cholangitis subsequent to coil migration in the lower bile duct. This situation was managed using endoscopic retrograde cholangiopancreatography (ERCP) allowing coil extraction with favorable evolution. CONCLUSIONS: GDA pseudo-aneurysms are very rare. Bleeding, secondary to the rupture of these lesions, is a serious complication that could lead to death. Diagnosis and treatment of ruptured GDA pseudo-aneurysms rely on angiography. This method is considered to be safe. Cholangitis secondary to coil migration in the main bile duct is exceedingly rare,but remains an eventuality that physicians should be cognizant of.